Simultaneous improvement and worsening of vitiligo lesions during the course of NB‐UVB phototherapy; vitiligo may not act as one unit. Issue 1 (9th September 2016) - Anbar, Tag; Abdel‐Rahman, Amal; Hegazy, Rehab; El‐Khayyat, Mohamed; Ragaie, Maha
Abstract: Re‐pigmentation and stabilization are the two ultimate goals of any re‐pigmenting plan designed for vitiligo management. Furthermore, whether the improvement of some vitiligo lesions could be considered a guarantee for a similar response and/or stabilization of the rest of the lesions or not, remains to be clarified. To evaluate the behavior of non‐segmental vitiligo (NSV), while on narrow band‐ultraviolet B (NB‐UVB) phototherapy. 25 patients with stable generalized NSV were included and received NB‐UVB twice weekly. For the sake of ensuring accuracy of follow up, up to four lesions were randomly chosen in each patient and regularly measured using the point counting technique. The over‐all point counting technique of all included patients showed a significant reduction (18.5 ± 8.4 cm 2 to 8.2± 3.1 cm 2 ) after 6 months of therapy ( p  < .001). Nine patients (36%), showed mixed response in the different lesions. Improvement was documented in some lesions, while other lesions showed no response or even worsening. No significant correlations were detected between the behavior of vitiligo during NB‐UVB and any of the demographic or clinical data of the patients. NB‐UVB is a pillar in the management of vitiligo, however close follow‐up of the patient as a whole and his lesions, by both subjective and objective measures are mandatory to detect activity as early as possible, as vitiligo at many times may not act as one unit. This early detection of activity and the subsequent change in the treatment policy may ultimately change the final outcome of treatment.